Study of the structural, thermal, rheological and film properties of functional copolymers of hydroxyethyl acrylate and methyl methacrylate (2016)
New functional polymers will be prepared using alkyd resins having high solid content (environmentally friendly) and comb-type structural morphology. Different copolymers of hydroxyethyl acrylate and methyl methacrylate (HEMMA) were synthesized by solution polymerization using azo-bis-(isobutyronitrile) (AIBN) as initiator and dimethylformamide as a solvent. The proportions utilized of AIBN were 0.5 (HEMMA1), 1.0 (HEMMA2), 1.5 (HEMMA3) and 2.0 wt. % (HEMMA4). The conversion percentage of the reaction was higher than 90%. The formation of the copolymers was evidenced by infrared analysis, hydroxyl value, and nuclear magnetic resonance. The intensity of OH group adsorption increased with the molecular weight and hydroxyl value. The polydispersity index was lower than 1.5. All copolymers exhibited a stable region on viscosity at a shear rate between 0.1 and 10 s–1. The copolymers exhibited good thermal stability, flexibility, and adherence.